44 SKELETAL MUSCLE ATROPHY, BONE LOSS, AND OXIDATIVE STRESS IN RATS WITH ALDOSTERONISM. Issue 1 (1st January 2007) - Neal, M.; Sun, Y.; Bhattacharya, S. K.; Ahokas, R. A.; Gerling, I. C.; Weber, K. T.
Abstract : Purpose: Congestive heart failure (CHF) is a syndrome composed of symptoms and signs arising from congested organs and hypoperfused tissues; it is mediated by a salt-avid state based on an activation of the circulating renin-angiotensin-aldosterone system (RAAS). Beyond this classic perspective, CHF also features a systemic illness with oxidative stress and progressive loss of soft tissues and bone that eventuates in a wasting syndrome termed cardiac cachexia. Pathophysiologic responses contributing to this illness are under investigation. Methods and Results: To simulate one aspect of RAAS activation and to address musculoskeletal health in aldosteronism, 8-week-old male Sprague-Dawley rats weighing 253 ± 11 g were treated for 4 weeks with aldosterone (ALDO, 0.75 μg/h) and 1% NaCl in their drinking water (ALDOST) to raise plasma ALDO levels to those found in human CHF. These levels are accompanied by secondary hyperparathyroidism (SHPT) due to ionized hypocalcemia and hypomagnesemia resulting from increased urinary and fecal excretion of Ca 2+ and Mg 2+ . We monitored body weight; skeletal muscle total Ca 2+, and morphology, including scarring (a marker of necrosis) and the presence of myocyte apoptosis (TUNEL assay); tibial bone mineral density (BMD) and content (BMC) and strength to flexor stress; plasma α1 -antiproteinase activity (AP), an inverse correlate of oxidative stress; and plasma parathyroid hormone (PTH). Compared with age-/gender-matched untreated controls, with ALDOST we found (mean ± SEM) inadequate weight gain (81 ± 5 vs 22 ±6 g), accompanied by increased ( p < .05) Ca 2+ concentration (8.1 ± 0.2 vs 11.0 ± 0.5 nEq/mg fat-free dry tissue) and an atrophy of skeletal muscle myocytes without evidence of apoptotic or necrotic cell death; a reduction ( p < .05) in BMD (0.121 ± 0.001 vs 0.115 ± 0.002 g/cm 2 ) and BMC (0.337 ± 0.009 vs 0.285 ± 0.007 g) associated with a fall ( p < .05) in bone strength (161.6 ± 7.8 vs 133.4 ± 4.8 MPa); a reduction in plasma α1 -AP activity (39.8 ± 2.1 vs 24.3 [138} 1.2 μmol/L) in keeping with the presence of oxidative stress at a systemic level; and increase in plasma PTH (10.6 ± 0.9 vs 16.0 ± 1.6 pg/mL). Conclusions: Aldosteronism in rats is accompanied by SHPT with skeletal muscle Ca 2+ overloading and atrophy, but not myocyte death, a loss of bone minerals with reduced strength to resist flexor stress, and the appearance of oxidative stress. In human CHF, aldosteronism may contribute to its progressive wasting.